Coevolutionary interplay: Helminths-trained immunity and its impact on the rise of inflammatory diseases - Carrera Silva, Eugenio Antonio (2025)
The gut biome, a complex ecosystem of micro- and macro-organisms, plays a crucial role in human health. A disruption in this evolutive balance, particularly during early life, can lead to immune dysregulation and inflammatory disorders. ‘Biome repletion’ has emerged as a potential therapeutic approach, introducing live microbes or helminth-derived products to restore immune balance. While helminth therapy has shown some promise, significant challenges remain in optimizing clinical trials. Factors such as patient genetics, disease status, helminth species, and the optimal timing and dosage of their products or metabolites must be carefully considered to train the immune system effectively. We aim to discuss how helminths and their products induce trained immunity as prospective to treat inflammatory and autoimmune diseases. The molecular repertoire of helminth excretory/secretory products (ESPs), which includes proteins, peptides, lipids, and RNA-carrying extracellular vesicles (EVs), underscores their potential to modulate innate immune cells and hematopoietic stem cell precursors. Mimicking natural delivery mechanisms like synthetic exosomes could revolutionize EV-based therapies and optimizing production and delivery of ESP will be crucial for their translation into clinical applications. By deciphering and harnessing helminth-derived products’ diverse modes of action, we can unleash their full therapeutic potential and pave the way for innovative treatments.